2004
DOI: 10.1002/bjs.4719
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial of continuous sutures or non-penetrating clips for radiocephalic arteriovenous fistula

Abstract: This randomized clinical trial provided further evidence that the use of vascular clips may improve the patency rate of radiocephalic arteriovenous fistulas for haemodialysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Such interventions include different types of anaesthetic procedures, balloon-assisted maturation, use of devices to connect the artery and the vein, ligation of accessory draining veins, dilatation of the main draining vein or specific surgical techniques to make the anastomosis. Two systematic reviews [36,37] and 16 RCTs assessing eight different interventions were identified [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53]. One systematic review and meta-analysis included six studies with 870 participants comparing the effects of regional versus local anaesthesia on several AV fistula outcomes [36].…”
Section: Rationale • Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Such interventions include different types of anaesthetic procedures, balloon-assisted maturation, use of devices to connect the artery and the vein, ligation of accessory draining veins, dilatation of the main draining vein or specific surgical techniques to make the anastomosis. Two systematic reviews [36,37] and 16 RCTs assessing eight different interventions were identified [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53]. One systematic review and meta-analysis included six studies with 870 participants comparing the effects of regional versus local anaesthesia on several AV fistula outcomes [36].…”
Section: Rationale • Backgroundmentioning
confidence: 99%
“…There were three RCTs that compared clips versus sutures in performing an end-to-side anastomosis for AV fistula creation [47][48][49]. All three found uncertain effects on primary patency or AV fistula maturation.…”
Section: Rationale • Backgroundmentioning
confidence: 99%
“…In 2004, Zeebregts reported a further randomized study on 107 radiocephalic fistulas using the same VCS, at that time marketed by Tyco health and Auto Suture Company, and Prolene. This study reported no significant difference in primary and primary‐assisted patency between the two groups …”
Section: Discussionmentioning
confidence: 57%
“…Laser-assisted vessel welding (LAVW) is an experimental technique that is being investigated as an alternative for suturing of end-to-end and end-to-side vascular anastomoses. The use of sutures, which currently comprises the gold standard approach, is associated with several drawbacks, including needle trauma, the introduction of exogenous materials (suture threads), induction of foreign body reactions, and leakage through the anastomosis [1][2][3][4]. Alternative mechanical closures, namely clips and tacks that are commonly used in minimally invasive and robotic cardiothoracic surgery, inflict more pronounced mechanical trauma and are associated with more extensive anastomosis-related bleeding.…”
Section: Introductionmentioning
confidence: 99%